The Relationship between Service Quality Perceptions and Expectations in Sporting Events with Loyalty of Esteghlal Team Fans - Azam Sadat Fallah Hosseini; Mohammad Eskandari; Asieh Adab; Reza Takdehghan; Hossein Sepasi (Asociación Española de Ciencias del Deporte, 2017)
In today very competitive market, achieving customer loyalty has become a key point for organizations management. In the field of sport, team loyalty is equal to consumer loyalty in the supply market. This study aimed to determine the relationship between service quality perceptions and expectations with fans loyalty. The current research method is descriptive, survey method and in term of purpose is an applied type. The study population consisted of Esteghlal team fans.  Identifying items of evaluating variables, the questionnaire contains 64 questions with a five-point Likert scale was designed to collect data. Cronbach's alpha coefficient was calculated 0.91 in a preliminary study based on the 25 questionnaires. After ensuring reliability and validity of scales designed according to our calculations, questionnaires with a sample size of 700 people were distributed in random sampling. After analyzing the data using Pearson correlation and regression coefficient, the results indicated a significant positive relationship between the variables of service quality perceptions, expectations and fans loyalty. In addition, the study suggested that the service quality perceptions and expectations in sporting event predict fans loyalty of Esteghlal team.